Assessment of the concentration of some heavy metals in bottom sediments in the coastal and island areas of the southern region, Vietnam - Duong, Phung Thai; Nhung, Pham Cam (Brawijaya University, 2024)
Rivers, such as the Dong Nai, Saigon, and Mekong, are subject to urban, industrial, and agricultural pollution, leading to a high risk of heavy metal accumulation in bottom sediments. With the aid of a boat and bucket as tools, a survey was conducted to collect sediment samples from the coastal areas (downstream of Dong Nai, Saigon, Mekong Rivers) and islands (Con Dao, Tho Chu) in the Southern region of Vietnam during April and May 2023. Out of a total of 35 samples collected, preserved according to the guidelines of the Ministry of Natural Resources and Environment, the heavy metal indicators were analyzed by atomic absorption spectroscopy, and the average heavy metal concentrations were in the following order: Zn>Cu>Cd>Pb>As. Compared with the Vietnamese Technical Regulation (QCVN 43:2017/BTNMT) on sediment quality and the sediment quality of the Canadian Environment Ministry, the heavy metal concentrations in the research area have not exceeded the specified standards. However, compared with standards from the USA, the Russian Federation, and other regions in Vietnam, the levels are quite high. Moreover, the Igeo index indicates that the concentration of Pb, As, and Cd at many coastal locations downstream of the rivers is heavily polluted. This evidences that in addition to pollution from upstream sources, the activities of the local population significantly contribute to the accumulation of pollution. The research results provide a scientific basis for limiting pollution sources to ensure sustainable development of the studied areas, which is necessary today.